The Effectiveness Of Coconut (Cocos nucifera) Soaking On The Masculinity Of Guppy Fish (Poecilia reticulata) - Naning Dwi Sulystyaningsih; Turmuzi Turmuzi; L. Achmad Tan Tilar WSK; Nuri Muahiddah; Luh Gede Sumahiradewi (University of Prof. Dr. Hazairin, SH, 2022)
Guppy fish (Poecilia reticulata) is an ornamental fish that is in great demand in the world market. One way to produce male fish is by the process of sex reversal from female to male (masculinity). This study aims to determine the effect of coconut water concentration on guppy fish (Poecilia reticulata) masculinity. The experiment used a completely randomized design (CRD), consisting of 4 treatments of coconut water concentration (P), namely 0% coconut water concentration (P1), 67% coconut water concentration (P2), 100% coconut water concentration (P3), and coconut water concentration 150% (P4). The study concluded that soaking guppy fish larvae using coconut water had a significant effect on the male genitalia of guppy fish. Guppy fish seeds soaked in coconut water with a concentration of 150% had the highest masculinity and survival rates, namely 91.1% and 97.7%. The water quality during maintenance was 27 – 28 0C, pH 7.2, and DO 3 – 6.8 mg/L.